2016
DOI: 10.1103/physrevd.94.114023
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of a jet with small radius

Abstract: In this paper we consider the fragmentation of a parton into a jet with small jet radius R. Perturbatively, logarithms of R can appear, which for narrow jets can lead to large corrections. Using soft-collinear effective theory, we introduce the fragmentation function to a jet (FFJ), which describes the fragmentation of a parton into a jet. We discuss how these objects are related to the standard jet functions. Calculating the FFJ to next-to-leading order, we show that these objects satisfy the standard Dokshit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(124 citation statements)
references
References 49 publications
2
122
0
Order By: Relevance
“…Since these logarithms are integrated over the specified parton kinematics together with the steeply falling parton luminosity, threshold logarithms can dominate the entire cross section in a wide kinematic range. Instead, the jet radius R is an external quantity and the dependence of the cross section is singlelogarithmic α n s ln k ðRÞ with k ≤ n instead of double-logarithmic [29][30][31]. The framework developed in [27] addresses both these logarithmic corrections on the same footing, and it was shown that numerically the threshold and the jet radius logarithmic terms do account for the dominant bulk of the NLO corrections.…”
Section: Introductionmentioning
confidence: 99%
“…Since these logarithms are integrated over the specified parton kinematics together with the steeply falling parton luminosity, threshold logarithms can dominate the entire cross section in a wide kinematic range. Instead, the jet radius R is an external quantity and the dependence of the cross section is singlelogarithmic α n s ln k ðRÞ with k ≤ n instead of double-logarithmic [29][30][31]. The framework developed in [27] addresses both these logarithmic corrections on the same footing, and it was shown that numerically the threshold and the jet radius logarithmic terms do account for the dominant bulk of the NLO corrections.…”
Section: Introductionmentioning
confidence: 99%
“…See also [22,23]. In this work, we perform the calculation of J/ψ mesons in jets where the observable is defined to be inclusive over the entire final state except for the observed jet [24][25][26][27]. This type of (semi-) inclusive observables are easily accessible by the experiments and a direct comparison between theory and data is possible.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13]. The so-called threshold logarithms arise near the exclusive phase space boundary, where the production of the signal jet just becomes possible.…”
mentioning
confidence: 99%